2012
DOI: 10.1002/hed.23126
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of human papillomavirus status, survivin, and epidermal growth factor receptor expression on survival in patients treated with radiochemotherapy for very advanced nonresectable oropharyngeal cancer

Abstract: HPV status influences PFS in patients with advanced, nonresectable tumor stages but not OS. Additional risk factors seem to have a stronger influence on survival than HPV status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
2
14
0
1
Order By: Relevance
“…The various cutoffs used for defining p16 overexpression have contributed to substantial variation in the level of concordance with direct HPV testing. The HPV and p16 concordance of our study is on the higher end (92%) among studies that employed the HPV DNA PCR approach (61-100%), but is similar to large studies (n > 100) with a defined p16 IHC cutoff of >50% (80-97% concordance) [17,22,[24][25][26][27][28][29]31,36,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. In a recent meta-analysis of OPSCC correlating HPV detected by DNA PCR and/or ISH and p16 (n = 2888), the highest correlation between HPV and p16 was for p16 IHC staining >70% rather than a verbal definition or a lower percentage.…”
Section: Discussionsupporting
confidence: 75%
“…The various cutoffs used for defining p16 overexpression have contributed to substantial variation in the level of concordance with direct HPV testing. The HPV and p16 concordance of our study is on the higher end (92%) among studies that employed the HPV DNA PCR approach (61-100%), but is similar to large studies (n > 100) with a defined p16 IHC cutoff of >50% (80-97% concordance) [17,22,[24][25][26][27][28][29]31,36,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. In a recent meta-analysis of OPSCC correlating HPV detected by DNA PCR and/or ISH and p16 (n = 2888), the highest correlation between HPV and p16 was for p16 IHC staining >70% rather than a verbal definition or a lower percentage.…”
Section: Discussionsupporting
confidence: 75%
“…In consequence, the majority of patients with T4a carcinoma treated in Germany are HPV-negative OPSCC. Our study is consistent with previous work that demonstrated worse survival rates for HPV-negative patients [5, 21, 25]. Although our results were not statistically significant, this can be attributed to the small number of p16-positive patients.…”
Section: Discussionsupporting
confidence: 92%
“…There are two explanations for this phenomenon: first, the relatively low proportion of HPV-related oropharyngeal carcinoma in Germany compared to other regions [25] and second, the advanced T category. Patients with HPV-related carcinoma are younger and more discerning and therefore seek medical help before the tumor becomes locally advanced (T4a) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in patients with advanced non-resectable tumors, HPV status had a positive impact on progression-free survival but not on overall survival [58]. This indicates that in subsets of HPV-related HNSCC, additional factors may overcome the influence of HPV, and stratification strategies have to be refined.…”
Section: Hpv Diagnostics Patient Survival and Treatmentmentioning
confidence: 99%